Indigenous rights, health and traditional medicine systems - Redvers, Nicole; Menzel, Kelly; Carroll, Danya; Zavaleta, Carol; Kokunda, Sylvia; Kobei, Daniel; Nelson Rojas, Juan (Bulletin of the World Health Organization, 2025)
The health of Indigenous Peoples around the world is tied to longstanding Indigenous knowledge practices and access to Indigenous traditional medicine systems. Indigenous communities continue to have concerns, however, about their ability to ensure intergenerational transfer of Indigenous traditional medicine knowledge. These concerns stem from the continued lack of Indigenous rights as a result of colonization, a lack of protection of land rights and different levels of Indigenous self-determination around the world, all of which affect traditional medicine access and practices. Indigenous Peoples' access to their traditional medicine systems will therefore continue to depend on their access to self-determination, land and cultural rights, as well as on Indigenous data sovereignty. A balanced approach to Indigenous health and well-being is needed that prioritizes Indigenous traditional practices, community involvement, and Indigenous cultural and language revitalization (with support for ongoing intergenerational knowledge transfer). These elements are important for bringing back ecological harmony to Indigenous Peoples, communities and the planet. Additionally, with sufficient resources and support, Indigenous Peoples and their concepts of health can be a blueprint for harmony for people and health systems more widely, with Indigenous Peoples being a key determinant of planetary health. We outline some key points to ensure that the concepts of health and well-being of Indigenous Peoples and their Indigenous traditional medicine systems are maintained going forward for individual, community and planetary health.